DRAMATURGI PADA GAYA HIDUP HEDONIS DI KALANGAN MAHASISWA (STUDI KASUS KAMPUS PANAM PEKANBARU) - Muhammad Iqbal; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was carried out in the campus area Panam District Tampan Pekanbaru City. The purpose of this research is to analyze the life of Hedonis students by using dramaturgy perspective. The theory used is the theory of dramaturgy by Erving Goffman. The technique of determining the sample by purposive sampling and set the number of samples as many as 4 people. The author himself uses qualitative descriptive method and data instrument is observation interview and documentation. The results of this study indicate that students who behave hedonically not necessarily a socially capable person, there are discreditabel stiga that they hide from the front of our stage of vision. In the dramaturgy of discreditabel stigma this is a bad thing that is hidden from the front of the stage itself, for example, he is a poor person, to cover the discreditabel stigma then he look neat, language-pretent like a movie star artist, when he walked the smell of his perfume smell everywhere so that the stigma was covered and the people on the front stage would think he was a rich man. That is the reality that occurs in most social interactions today, many people want to be considered a high social status but are not aware of the bitterness of real life reality, this tends to occur in adolescence. Wanting to get friends from the upper classes was forced to follow the high-class behavior of example. For example, buy one piece of T-shirts with a price reaching 400 thousand dollars. Of course, with rational thinking for those with difficult economics it is better to use the money for their primary needs such as for food needs. That is where the harmony happens not to think about the situation and conditions, like the saying of the big peg from the pole Keywords: Dramaturgy, Hedonic, Lifestyle of College Students